1999
DOI: 10.1038/sj.cr.7290016
|View full text |Cite
|
Sign up to set email alerts
|

The Notch-Hes pathway in mammalian neural development

Abstract: A wide variety of neurons and glial cells differentiate from common precursor cells in the developing nervous system. During this process, Notch-mediated cell-cell interaction is essential for maintenance of dividing cells and subsequent generation of cell type diversity. Activation of Notch inhibits cellular differentiation, and abnormality of the Notch pathway leads to premature neuronal differentiation, the lack of some cell types, and severe defects of tissue morphogenesis. Recent data demonstrate that Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
194
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(201 citation statements)
references
References 30 publications
7
194
0
Order By: Relevance
“…Several lines of evidence have suggested that these genes are indeed direct Notch target genes: a) The promoters of Hes1, Hes5 and Hes7 as well as Hey1, Hey2 and HeyL (subfamily of Hes, related with YRPW motif) can be activated by a constitutive active form of Notch1 [10 -12], reviewed in [7]; constitutive active Notch describes a mutant of Notch that is continuously proteolytically processed and migrating to the nucleus, b) endogenous Hey1 and Hey2 show an upregulation by NICD in several different cell lines [13], c) in co-culture experiments with Notch-ligand expressing cells, that achieve a more physiological level of Notch signaling, these genes are upregulated as well [13 -15]; these experiments were also performed in the presence of cyclohexamide, an inhibitor of protein synthesis, to exclude secondary effects, d) k-secretase inhibitor DAPT, which prevents cleavage of Notch, was added to Tcell leukemia cell lines which show constitutive-active Notch signaling; subsequent microarray analysis identified again members of this transcription factor family as direct Notch target genes [16]. Therefore, in mammals, the best-described Notch target genes are indeed the transcription factors Hes1, Hes5 and Hey1 [8,17]. Hes and Hey proteins are helix-loop-helix transcription factors that function as transcriptional repressors.…”
Section: Notch Target Genesmentioning
confidence: 99%
“…Several lines of evidence have suggested that these genes are indeed direct Notch target genes: a) The promoters of Hes1, Hes5 and Hes7 as well as Hey1, Hey2 and HeyL (subfamily of Hes, related with YRPW motif) can be activated by a constitutive active form of Notch1 [10 -12], reviewed in [7]; constitutive active Notch describes a mutant of Notch that is continuously proteolytically processed and migrating to the nucleus, b) endogenous Hey1 and Hey2 show an upregulation by NICD in several different cell lines [13], c) in co-culture experiments with Notch-ligand expressing cells, that achieve a more physiological level of Notch signaling, these genes are upregulated as well [13 -15]; these experiments were also performed in the presence of cyclohexamide, an inhibitor of protein synthesis, to exclude secondary effects, d) k-secretase inhibitor DAPT, which prevents cleavage of Notch, was added to Tcell leukemia cell lines which show constitutive-active Notch signaling; subsequent microarray analysis identified again members of this transcription factor family as direct Notch target genes [16]. Therefore, in mammals, the best-described Notch target genes are indeed the transcription factors Hes1, Hes5 and Hey1 [8,17]. Hes and Hey proteins are helix-loop-helix transcription factors that function as transcriptional repressors.…”
Section: Notch Target Genesmentioning
confidence: 99%
“…1 The principal targets of Notch are the members of the Hairy and Enhancer of Split (HES) family of transcriptional repressors. 2 Activation of Notch has been associated with different types of human cancer such as intestinal carcinomas, gliomas, neuroblastomas 3,4 and leukemias. 4 Specifically, activating mutations of Notch1 have been found in about 50% of human T-ALL.…”
Section: Introductionmentioning
confidence: 99%
“…In the Notch-activated cells, Hes1 and Hes5 are induced and repress both the expression and activity of Mash1, and then neuronal differentiation is inhibited. This signaling process, so-called "lateral inhibition," maintains the number and status of undifferentiated neural progenitors and neural stem cells in the developing central nervous system (21). In this process, Hes6 can antagonize the activity of Hes1 or Hairy 1/2 to promote neurogenesis (22)(23)(24).…”
mentioning
confidence: 99%